Global Extent of Early Eocene Hyperthermal Events: A New Pacific Benthic Foraminiferal Isotope Record From Shatsky Rise (ODP Site 1209). Issue 6 (30th June 2018) - Westerhold, T.; Röhl, U.; Donner, B.; Zachos, J. C.
Abstract: Studying the dynamics of past global warming events during the late Paleocene to middle Eocene informs our understanding of Earth's carbon cycle behavior under elevated atmospheric pCO2 conditions. Due to sparse data coverage, the spatial character of numerous hyperthermal events during this period is still poorly constrained. Here we present a high‐resolution, benthic foraminiferal stable isotope record for northwest Pacific ODP Site 1209 (Leg 198) spanning 44 to 56 Ma with 5 kyr resolution. An existing Paleocene section was extended into the middle Eocene creating an unprecedented 22 Myr single‐site record. Several identified carbon isotope excursions correspond in timing and magnitude to hyperthermal layers previously described elsewhere. Maxima in scanning X‐ray fluorescence Fe intensities and pronounced minima in the wt% coarse fraction characterize carbonate dissolution for all of the hyperthermal events. The new astronomically calibrated stable oxygen isotope record assists in defining the onset, duration, and demise of the Early Eocene Climate Optimum (EECO, 49.14 to 53.26 Ma) and the onset of global cooling after the EECO (49.14 Ma). The cooling trend was interrupted by two warming episodes at 47.2 and 46.7 Ma. A major positive shift in the benthic foraminiferal carbon isotope record occurring from 51.2 to 51.0 Ma is now confirmed to be global. Benthic foraminiferal δ 13 C records from Atlantic and Pacific Oceans converge from 52.0 to 47.5 Ma pointing to a closer connection of deepwater convection initiating well in advance of the final connection ~40 Ma ago or an increase in bottom water formation around Antarctica. Key Points: Early Eocene hyperthermal events occur globally A 22‐Myr astronomically calibrated benthic foraminiferal stable isotope record at 5‐kyr resolution from the northwest Pacific is formed Major positive shift in benthic carbon isotope data within Chron C23n coincides with the global reorganization of the plate‐mantle system